Recent Advance in Source, Property, Differentiation, and Applications of Infrapatellar Fat Pad Adipose-Derived Stem Cells - Yu-chen Zhong; Shi-chun Wang; Yin-he Han; Yu Wen (Hindawi Limited, 2020)
Infrapatellar fat pad (IPFP) can be easily obtained during knee surgery, which avoids the damage to patients for obtaining IPFP. Infrapatellar fat pad adipose-derived stem cells (IPFP-ASCs) are also called infrapatellar fat pad mesenchymal stem cells (IPFP-MSCs) because the morphology of IPFP-ASCs is similar to that of bone marrow mesenchymal stem cells (BM-MSCs). IPFP-ASCs are attracting more and more attention due to their characteristics suitable to regenerative medicine such as strong proliferation and differentiation, anti-inflammation, antiaging, secreting cytokines, multipotential capacity, and 3D culture. IPFP-ASCs can repair articular cartilage and relieve the pain caused by osteoarthritis, so most of IPFP-related review articles focus on osteoarthritis. This article reviews the anatomy and function of IPFP, as well as the discovery, amplification, multipotential capacity, and application of IPFP-ASCs in order to explain why IPFP-ASC is a superior stem cell source in regenerative medicine.